The integration of Latin American bond markets: a copula analysis approach (1999-2015). (2016) - Ortiz, Edgar; López-Herrera, Francisco; Santillán-Salgado, Roberto J.; Fonseca-Ramírez, Alejandro
This paper examines the relationships among government bonds markets, represented by EMBI returns for six Latin American markets: Argentina, Brazil, Chile, Colombia, Mexico and Peru. It applies a bivariate copula approach that identifies by pairs of markets the importance of that relationship. The sample data includes EMBI information about the six most important Latin American bond markets, including, Argentina, Brazil, Chile, Colombia, Mexico and Peru. Daily data covers the period May 28, 1999 to May 13, 2008. The empirical evidence shows that the association among these markets remains partially segmented. These results suggest that there are good opportunities to take advantage of diversification for investors' portfolios. Additionally, from the point of view of policy makers this evidence suggests that independently of any integration scheme, each country should strengthen their own macroeconomic policies, particularly their monetary policies. Finally, for corporations in the region results of this work, i.e., market segmentation of their respective bond markets implies less liquidity and efficiency of their domestic markets, as well as restricted opportunities for corporate regional cooperation.